Fineline Tattoo Design as a Form of Self Expression at Ingkeu Ink Tattoo Studio - Fauzi, Ivan; Tjokropramono, I Gede Yosef; Mustika, I Ketut (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
The main objective of this research and art creation is to create and present the work "Designing Fineline Tattoos as a Form of Self-Expression at Ingkeu Ink Tattoo Studio" as a representation of arts and culture education. Fineline tattoo is a style of tattoo that involves creating a design with very thin and smooth lines. These tattoos are often minimalist and subtle, with intricate and detailed designs that require a skilled artist to execute. This creation is research-based, so the method consists of two inseparable parts, namely the research method and the creation method. The technique for implementing MBKM internship/work practice activities at Ingkeu ink tattoo studio is carried out using a project based learning model. In designing this tattoo design, it begins with brainstorming together to collect the concepts and topics that will be discussed. After getting a mature concept, students can continue to the stages of the work process. In this research the author will describe the Fineline Tattoo design process as a form of self-expression at Ingkeu ink tattoo studio along with an analysis of the design results. The data in this research was obtained directly from Ingkeu ink tattoo studio as a partner who has a project to be featured in the internship report using several methods. The results of the tattoos done by the author are also uploaded by partners on social media and TikTok, in this way the partners believe they are very effective in attracting client interest.